2002
DOI: 10.1111/j.1527-3458.2002.tb00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Profile of Enoxaparin, a Low Molecular Weight Heparin, in In Vivo Models of Cerebral Ischemia or Traumatic Brain Injury in Rats: a Review

Abstract: The development of treatments for acute neurodegenerative diseases (stroke and brain trauma) has focused on (i) re-establishing blood flow to ischemic areas as quickly as possible (i.e. mainly antithrombotics or thrombolytics for stroke therapy) and (ii) on protecting neurons from cytotoxic events (i.e. neuroprotective therapies such as anti-excitotoxic or anti-inflammatory agents for stroke and neurotrauma therapies). This paper reviews the preclinical data for enoxaparin in in vivo models of ischemia and bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 75 publications
(76 reference statements)
2
35
1
1
Order By: Relevance
“…4 A-D). Intravenous injections of Enoxaparin are neuroprotective in animal models of stroke and neurodegenerative diseases (26)(27)(28), and our results indicate that Enoxaparin may also be worthy of assessment as HD therapeutics. Recently, a number of biologically active Food and Drug Administrationapproved heterocyclic, tricyclic, and phenothiazine-derived compounds have been identified as putative MPTP blockers (21).…”
Section: Discussionmentioning
confidence: 95%
“…4 A-D). Intravenous injections of Enoxaparin are neuroprotective in animal models of stroke and neurodegenerative diseases (26)(27)(28), and our results indicate that Enoxaparin may also be worthy of assessment as HD therapeutics. Recently, a number of biologically active Food and Drug Administrationapproved heterocyclic, tricyclic, and phenothiazine-derived compounds have been identified as putative MPTP blockers (21).…”
Section: Discussionmentioning
confidence: 95%
“…enoxaparin) in rodent models of MCA occlusion, have shown significantly decreased in residual volumes of infarction and improvement in behavioral outcome. (Stutzmann et al, 2002) Early studies in the non-human primate had already shown that heparin (and ticlopidine in combination) could significantly reduce the density of microvessel occlusions in the ischemic territory. Those studies suggest that by limiting coagulation system activation, and blocking the effects of endothelial cell activation, the effects of Virchow’s triad can be reduced.…”
Section: 0 Effects Of Ischemia On Vascular Elements Within the Neurmentioning
confidence: 99%
“…Although the initial trigger of the brain damage induced by the mechanical strike in TBI is different from stroke, the pathological signaling pathways and the consequent cell death mechanisms in TBI share some similarities with ischemic strokes, and there is often a second ischemic damage after the initial TBI insult (Bramlett and Dietrich, 2004; Simard et al, 2010; Stutzmann et al, 2002). Specifically, regional ischemia is one of the main events in TBI secondary injury due to the damage to vasculatures (Simard et al, 2010; Stutzmann et al, 2002). It is also well characterized that excitotoxicity and apoptosis are mainly responsible for neuronal damage in both ischemic stroke and TBI (Liou et al, 2003).…”
Section: Introductionmentioning
confidence: 99%